2020
DOI: 10.14712/18059694.2020.14
|View full text |Cite
|
Sign up to set email alerts
|

Interdisciplinary Management of Visceral Artery Aneurysms and Visceral Artery Pseudoaneurysms

Abstract: The paper presents the results of treating 14 patients, namely eight patients with visceral artery aneurysms and six patients with visceral artery pseudoaneurysms. In 64.3% of the patients, the initial diagnosis was made based on the ultrasound examination. All the patients (100%) underwent CT angiography, while angiography was performed in 71.4% of the cases. Five (35.7%) patients with visceral artery pseudoaneurysms were emergently hospitalized; among them, the signs of bleeding were observed in 2 patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 23 publications
0
1
0
8
Order By: Relevance
“…Debate remains for years on the consensus for the first-line therapy for lesions that are both suitable for open and endovascular surgery. We summarized publications of SMAA with at least three cases in recent 10 years 11 , 3032 (Table 5), and found that first-line therapy and reporting standard varies between different centers, which, to some degree, indicate the lack of a powerful guideline and also the complex and individual nature of SMAA. However, a trend toward endovascular surgery is emerging.…”
Section: Discussionmentioning
confidence: 99%
“…Debate remains for years on the consensus for the first-line therapy for lesions that are both suitable for open and endovascular surgery. We summarized publications of SMAA with at least three cases in recent 10 years 11 , 3032 (Table 5), and found that first-line therapy and reporting standard varies between different centers, which, to some degree, indicate the lack of a powerful guideline and also the complex and individual nature of SMAA. However, a trend toward endovascular surgery is emerging.…”
Section: Discussionmentioning
confidence: 99%
“…Большинство ПА протекают бессимптомно и выявляются при динамическом наблюдении за пациентом с травмой или при обследовании по поводу других заболеваний [2,4,8]. Разрыв внепеченочной аневризмы сопровождается внутрибрюшным кровотечением [5].…”
Section: клинические наблюдения и краткие сообщенияunclassified
“…Симптомы, характерные для кровотечения из верхних отделов ЖКТ, -тошнота, рвота кровью или «кофейной гущей», мелена, при обильном кровотечении -выделение алой крови из прямой кишки, гемодинамическая нестабильность. Они могут встречаться изолированно у 42 % больных [5,8,12].…”
Section: клинические наблюдения и краткие сообщенияunclassified
See 2 more Smart Citations